Enhancing the supply chain performance of Kayumas specialty coffee based on the SCOR-ANP approach - Risanda, Aisya; Muhaimin, Abdul Wahib; Maulidah, Silvana (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: Performance evaluation is essential in defining supply chain strategies because the firm can find out how the business processes in the supply chain are running and formulate strategic policies. Kayumas coffee is one of Indonesia’s specialty coffee with a unique aroma and flavor originating from Kayumas Village, Situbondo District, East Java. Kayumas coffee supply chain needs to be evaluated because of the lack of competitiveness with other specialty coffees. Strategies are needed to improve supply chain performance, improve product quality, and reduce costs. This study aims to configure the supply chain of Kayumas specialty coffee structure, evaluate its performance, and determine performance improvement strategies. Methods: This study uses descriptive analysis to configure the supply chain structure and flow. Analysis of supply chain performance based on Supply Chain Operation Reference (SCOR) model then weighted with Analytic Network Process (ANP). Performance improvement strategies were formulated by a discussion with experts and then weighted with ANP. Results: The research results show that the Kayumas specialty coffee supply chain comprises farmers, farmer groups, distributors or resellers, and consumers. There are 6 performance indicators (metrics) to measure performance: perfect order fulfillment, order fulfillment cycle time, flexibility, total supply chain management cost, cost of goods sold, and cash-to-cash cycle time. Performance measurement shows that Kayumas specialty coffee supply chain performance is in the inferior category. Conclusion: The strategy needed to improve supply chain performance by reducing cost is a partnership between supply chain members to reach a price agreement.